Athar Istikhdam Manhaj Take And Give Fi Nata’ij Ta’allum Maddah Al-Fiqh Li Tullab Al-Fasl Al-Thamin Bi Al-Madrasah Al-Thanawiyah Al-Muhammadiyyah 9 Watukebo Jember Al-‘Am Al-Dirasi 2019/2020 - Miftahul Ulum; Muhammad Abdul Basit (IAIN Ponorogo, 2020)
Abstrak: The ability of students mastery influenced by a variety of factors. Omar H. Malik mentions there are influenced factors by both the absence of teachers in teaching. The more quality learning in the classroom, it is assumed the better, would affect the grades and student learning outcomes in the subject. There are many strategies of active learning is the strategy of give and take. This Strategy has characteristics that could improve the process quality of independent learning. Writing is aiming to know how effectiveness of strategies take and give to improve the outcomes of learning in the material Fiqh at SMP Muhammadiyah Watukebo Jember East Java. This research using quantitative method, type of experiment by comparing student learning outcomes in the experimental group and the control group. The result of t-test is performed which shows the Sig. (2-tailed) of 3.048˃ 0.003. It is showing the effectiveness of the method take and give in improving outcomes of learning Fiqh at SMP Muhammadiyah Watukebo Jember Java East.Abstrak: Kemampuan penguasaan siswa terhadap mata pelajaran dipengaruhi oleh berbagai faktor. Umar H. Malik menyebutkan di antaranya dipengaruhi oleh baik tidaknya guru dalam mengajar. Semakin berkualitas pembelajaran di kelas, diasumsikan semakin baik nilai dan hasil belajar siswa pada mata pelajaran tersebut. Terdapat banyak strategi pembelajaran aktif, salah satu di antaranya adalah strategi take and give. Strategi ini memiliki karakteristik yang dapat meningkatkan mutu proses pembelajaran secara mandiri. Tulisan ini bertujuan ingin mengetahui efektivitas strategi Take and Give dalam meningkatkan hasil belajar siswa pada materi Fiqh di SMP Muhammadiyah Watukebo Jember Jawa Timur dengan menggunakan pendekatan kuantitatif jenis eksperimen. Hasil uji-t yang menunjukkan nilai Sig. (2-tailed) sebesar 3,048˃0,003. Hal ini menunjukkan efektivitas metode take and give dalam meningkatkan hasil belajar materi Fiqh di SMP Muhammadiyah Watukebo Jember Jawa Timur.